Uncertainty quantification of the effect of concrete heterogeneity on nonlinear seismic response of gravity dams including record-to-record variability. (December 2021) - Liu, Pengfei; Chen, Jianyun; Fan, Shuli; Xu, Qiang
Abstract: Although the effects of the concrete heterogeneity on the seismic response of concrete gravity dams have been explored based on random finite element method, the results of different studies vary greatly and there are few quantitative studies on the effects. In addition, the correlation between concrete modulus and strength is usually ignored, which is a departure from the reality. In this study, the effects of the concrete heterogeneity on the nonlinear seismic response of concrete gravity dams under different input ground motions are systematically studied based on random field theory. The dispersion and uncertainty of the seismic responses and the damage pattern are quantified. In addition, the effects of the correlation between concrete modulus and strength are also investigated and quantified based on the cross-correlated random fields simulation method. It is found that the effects of the concrete heterogeneity on the nonlinear dynamic response of concrete dams are strongly dependent on the input seismic motions, which provides an explanation for the conflicts in the previous studies. The results also show that the correlation between concrete modulus and strength has important effects on the dispersion of the seismic response and damage pattern of concrete gravity dams. Under certain ground motions, ignoring the correlation may underestimate the failure probability of the dams.